Model 5D Gedung Dekanat dan Perkuliahan Fakultas Kesehatan Masyarakat, Universitas Diponegoro - Firdaus, Muhammad Ar Rayyan; Asalina, Rahma Uyun; Nurdiana, Asri; Setiabudi, Bambang (Jurnal Sipil dan Arsitektur, 2023)
Redesign is the critical point of the construction process which aims to provide technical specification requirements that will be used at the project later. In project planning, more time and accuracy are needed to obtain the required output. Therefore, it is necessary to use BIM or Building Information Modeling software to simplify, speed up and minimize errors due to human error. This Project was made a redesign the Dean's Building and Lecture project of the Faculty of Public Health, Diponegoro University using the BIM or Building Information Modeling application which aims to streamline structural, planning work, financing estimation, and scheduling processes. The method used is a literature study with the main data of design drawing and others data from the construction project of the Dean Building and Lectures of the Faculty of Public Health, Diponegoro University. The preparation of this Project goes through 3 stages. The first stage is to redesign the FKM Building project using Autodes Revit, the second stage is analyzing the structure with SAP 2000 and Ms Excel applications then the third stage is replanning cost estimation and scheduling using Ms Excel and Ms Project. The result of this Final Project is to obtain new best drawings, material specifications, cost estimation and scheduling.